THE COMPARISON OF LANGUAGE SKILLS BETWEEN MALE AND FEMALE STUDENTS USING THE BOOK "FROG, WHERE ARE YOU?" BY MERCER MAYER - Tyas Desita Wengrum; Adhi Nurhartanto; Meutia Rachmatia (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
This research focuses on students' language learning in 5th grade primary school. The research project examines on the language learning of 5th grade primary school learners.  The focus is to compare the linguistic skill of male and female learners by taking retelling stories using Indonesian language.  The factor used in this research is grammatical cohesion analysis which examines all grammatical aspects which includes sentence, clause, grammatical errors, emotive word, and interference. Data was gained through a controlled observation and analysed using the contrasting descriptive method which looks how male and female learners construct sentences and clauses, as well as the grammar mistakes they make.  5th grade male learners of Integrated Islamic Elementary School Al Abidin Surakarta were discovered to be more proficient in using Indonesian than female students were. Female students tend to make fewer grammatical errors than male learners when reciting Indonesian stories.  Male learners, on the other hand, are more imaginative and use emotive language frequently, indicating that male learners are more expressive while telling stories.  According to the data, male learners were more proficient in using Indonesian than female learners.  When narrating stories, female learners make fewer errors in grammar.  It also shows a lack of emotional connection.  It may be fair to say that male learnersâ€™ proficiency in telling stories is better than the female learnersâ€™ due to their expressiveness in telling the language but female learners are more structured in producing their language